Quality of Life Biopsychosocial Perspectives - Irtelli, Floriana; Durbano, Federico; George Taukeni, Simon (IntechOpen, 2020)
This book is a collection of chapters addressing various aspects of quality of life and health psychology from a biopsychosocial perspective. Chapters cover crucial issues, both clinical and social. Starting with an analysis of the concept of quality of life as it is described by the World Health Organization, subsequent chapters of the book examine the biological, psychological, social, and spiritual issues related to the concept. The book explores how health, climate, psychiatric diseases, and social conditions of specific geographical areas can impact quality of life.